PELATIHAN BERPIKIR DIVERGEN MELALUI PERTANYAAN DAN TUGAS-TUGAS IMAJINATIF UNTUK MENGEMBANGKAN KREATIVITAS ANAK - Mardiyati, Siti; Wahyuningsih, Siti; Hardjajani, Tuti (Jurnal Inovasi Pendidikan, 2011)
This study aims to determine: (1) the influence of divergent thinking training that is designed in a question and imaginative tasks, to improve the creativity of children. (2) To determine the influence of divergent thinking training is packaged in a question and imaginative tasks, can provide the atmosphere of excitement as the atmosphere of playing in children. The experiment was conducted in kindergarten Aisyiah Premulung Laweyan Surakarta in Academic Year 2009/2010. The subject of this study was student class B shares of 30 children. According to the study design or design of this study include Pre Experimental Design, also called quasi experiment, with the pattern: Pre-test and Post-test Design Group One as a data collection technique using keativitas test tech-niques to test the first hypothesis to test, while the second hypothesis using a technique observations with the instruments of observation and completed documentation form (photo). Based on statistical analysis to test the first hypothesis got result to> tt = 4.651> 2.76 (db.29), this means that the hypothesis that divergent thinking training that is designed in the questions and imaginative tasks, to improve the creativity of children TK, verified. Furthermore, to test the second hypothesis, based on the observation (teacher notes) and documentation (photos) records of activities, it can be concluded that divergent thinking pelafihan packaged in a question and imaginative tasks, proved to give the atmosphere of excitement as the atmosphere of playing in kindergarten.